VARIASI ISOLEK KERINCI: PENDEKATAN AUTOMATED SIMILARITY JUDGEMENT PROGRAM (ASJP) DATABASE - Aryoni Ananta; Fadlul Rahman; Santi Kurniati (Kajian Linguistik dan Sastra, 2023)
Kerinci is located in Jambi Province and is bordered by the West Sumatra Province. The language used by the people of Kerinci, in general, is the Kerinci language with very diverse isolect variants. This research was conducted in three areas of Kerinci, namely, Tanah Kampung, located in Sungai Penuh City, Kemantan Raya, and Dusun Baru, located in Kerinci Regency. The fundamental reason for conducting this research is to document the variation of isolects in Kerinci from the Automated Similarity Judgment Program (ASJP) Database. This is very important to do considering that so many indigenous languages have shifted or become extinct due to the current technological revolution. The method used is a descriptive method with a dialectological approach, and the technique used is the technique of recording and interviewing using the ASJP database. From the research that has been done, it can be seen that these three observation areas have very diverse phonological variations phonologically. However, when viewed from a lexical point of view, only 11.66% of lexical variations and 88.33% of lexical were found to be the same or similar.Keywords: ASJP, Isolect, Kerinci, Sound Variations